Rememorando vidas: lembranças de velhos trabalhadores - Poltronieri, Cristiane de Fátima [UNESP] (2014)
This study aims to know the memory of elder people, mainly the memory of their work done in footwear factories in Franca/SP. The work seeks to discuss the memories and experiences that are often missed by not valuing the past. So we decided to analyze the memory of four elderly people who are in the Elderly Community Centre Lions Sobral (in Portuguese, known as (CCI) Centro de Convivência do Idoso Lions Sobral), as well as the position of the social worker of this institution upon the subject of remembering the past. The memoirists‟ narratives highlighted the memories about the time and in time, resulting in three areas of analysis: the lifetime memory, the work memory and family and old age memory. Thus, research has focused on discussions about human aging, the world of work and the memory and the recovery of the elder‟s experiences by other generations. It was also highlighted a brief overview of the elderly population in Franca city and the profile of CCI Lions Sobral participants. The study was based on quantitative and qualitative research approach, using the method of oral history from the life history perspective for the elderly, and of the semi-structured interview for the social worker. The data analysis was done through the theoretical and methodological principles of dialectical historical materialism. Therefore, the survey analyzes the reality presented in the older workers‟ narratives, considering and valuing the life stories brought by his memories